EMOTIONAL QUESTION VERSUS INTELLIGENCE QUESTION AND INTEREST LEARNING AS A MODERATING VARIABLE (A CASE STUDY OF COMPUTERIZED ACCOUNTING LEARNING IN THE FACULTY OF ECONOMICS) - Hafsah UMSU; Syafrida Hani (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
ABSTRACTThe purpose of this study is to determine whether the Intelligence Question (IQ) and Emotional Question (EQ) affect the understanding of computerized accounting learning partially and simultaneously on the students of accounting program faculty of economics University of Muhammadiyah Sumatera Utara (UMSU) Medan with the interest of learning as a moderating variable. The sample of research is determined by purposive sampling with the criterion of accounting student of fourth semester of Faculty of Economics UMSU. The number of samples by purposive sampling is 60 respondents. The data collected were primary data obtained through questionnaires and tested intelligence. Using Multiple Regression analysis, t-test and F-test does data processing. The results of research Partially significant variables are EQ variables affect the level of student understanding of the subject of accounting computerization, while the IQ variables have no significant effect. Simultaneously the variables of IQ and EQ affect the level of understanding of computerized accounting learning. Learning interest variables as moderating variables also influence the level of understanding of computerized accounting learning. In addition, learning interest variables also serve as moderating to the relationship between the variables of EQ on the level of understanding computerized accounting learning. Thus the interest variable performs its function as moderating variable.